A report of teachers’ opinions toward using smart tablets as learning and teaching tools by teachers and students in two government model schools in Dubai - Alabd, Ayesha Ahmad (2014)
Educators and stakeholders couldn’t ignore the technology deep impact on young children and adult. It becomes the government of the UAE priority. The ministry of Education introduced Education Vision 2020 which emphasizes the use of advanced education techniques including the new technologies. Smart tablets have been applied in numbers of schools, so they tend to utilize the smart tablets as the main day-to-day teaching resource for introducing and practicing the context. This study examines teachers’ opinions toward using smart tablets as learning and teaching tools in two model schools in Dubai. The research demonstrates the different approaches related to the selected area. This research asks the following questions, the first one is the What are teachers opinions and attitude about using smart tablets as learning and teaching tools in the classroom. The second is What kinds of tasks do teachers and students typically use smart tablets in the classrooms for. The third one is What do subjects teachers views about the positives and negatives of using smart tablets in classes. The results have shown their the teachers positive attitude toward the result of applying the smart tables as a teaching tool.